High-dose therapy with peripheral blood progenitor cell transplantation in multiple myeloma - Goldschmidt, Hartmut; Hegenbart, Ute; Wallmeier, M.; Hohaus, Stefan; Engenhart, Rita; Wannenmacher, Michael; Haas, Rainer (Annals of oncology, 1997)
Background - The objective of our study was to evaluate the efficacy and toxicity of a high-dose melphalan-based (HDMel) therapy with or without total body irradiation (TBI) followed by peripheral blood progenitor (PBPC) transplantation in patients with multiple myeloma (MM). - Patients and methods - Between June 1992 and May 1996, 100 patients (67 males/33 females) with a median age of 51 years (range 30-65) were transplanted at our centre. PBPC were collected during G-CSF-enhanced leukocyte recovery following high-dose chemotherapy. Fifty patients were treated with TBI + melphalan 140 mg/m2, while 50 patients received melphalan 200 mg/m2. - Results - Following PBPC autografting, the median time to reach platelets ≥20 × l09/1 and neutrophils ≥0.5 × l09/1 was 11 and 14 days with no difference between the treatment groups. In the TBI group significantly longer periods of total parenteral nutrition were required due to severe mucositis. Two patients from the TBI group died due to transplantation related complications. Following high-dose treatment, remission state improved in 43 out of 98 patients. No statistically significant advantage in reaching CR or PR was observed with TBI + HD-Mel compared to the treatment with HD-Mel alone. - Conclusion - Dose-escalated treatments, with particular regard to the inclusion or omission of TBI, should be prospectively investigated to find the best high-dose regimen.
Elektronische Reproduktion der Druck-Ausgabe 6. Januar 2020
Gesehen am 24.04.2025